Human Capital Development through Training, Rewards, and Education: Implications for Employee Performance with Work Environment as a Moderator at PT Lautan Makmur Sentosa - Lukiyana, Lukiyana; Frasasty, Eka (CV. Tripe Konsultan, 2025)
This study aimed to analyze the influence of job training, reward systems, education level, and the work environment on employee performance, as well as to examine the moderating role of the work environment. A quantitative research design was employed using a survey approach involving 125 employees of PT Lautan Makmur Sentosa. Data were collected through a validated and reliable questionnaire and analyzed using SmartPLS (Partial Least Squares). The findings reveal that job training, reward systems, and education level each have a positive and significant effect on employee performance, highlighting the importance of training programs, appropriate reward mechanisms, and adequate educational qualifications in improving performance. The work environment also demonstrates a strong positive influence on employee productivity. Furthermore, the moderating analysis shows that the work environment strengthens the positive relationship between job training and employee performance but weakens the relationship between reward systems and performance. Meanwhile, the interaction between education level and work environment indicates that a more conducive work environment enhances the performance of employees with higher educational backgrounds. These results suggest that the interplay between work environment conditions and human capital factors requires careful managerial attention. Overall, this research provides valuable insights for companies in designing effective human resource strategies to optimize employee performance.